Large-scale Social Restrictions: What's Next? - Namira Ivanka (The Indonesian Journal of International Clinical Legal Education, 2020)
In the middle of the COvid-19 Pandemic, in addition to social distancing, the government is intensively preventing the spread of the corona virus, as we know that the corona virus is a very scary virus for many people. The virus has spread more and more every day and the way it is spread is very easy and can attack anyone and does not thicken the ages ranging from toddlers to the elderly can be exposed to this Covid-19 virus. Although this virus has a relatively low mortality rate. But who would have thought the spread was faster than other viruses. Until now the world is still racing to find a cure for this corona virus. Therefore, the government issued a policy so that it could immediately break the chain of the spread of the virus by means of large-scale social restrictions. And when large-scale social restrictions are implemented in an area to stop the spread of the corona virus (Covid-19), all activities are restricted. The enactment of large-scale social restrictions aims to fulfill the criteria for disease situations in the form of a significant increase in the number of cases and / or deaths from disease, rapid spread of cases to several regions, and there are epidemiological links with similar events in other regions or countries.